Reexaming the link between instability and growth in Latin America: A dynamic panel data estimation using K-median clusters - Bermúdez, Cecilia (2015)
We estimate a dynamic panel data model to assess the relationship between different levels of instability—proxied by growth volatility and inflation— and growth in Latin America from 1960 to 2011. Outlying observations could be mistakenly treated as thresholds or regime switch. Hence we use k-median clustering to mitigate the outlier problem and properly identify "scenarios" of instability. Our key findings are that while high inflation is harmful, low inflation is in fact positively related to growth. Volatility is also found to be significant and negative, but with no differential effect— between low and high levels—on growth.